Effect of foliar application of aminoacids on plant yield and physiological parameters in bean plants irrigated with seawater (2015)
Salinity decreases yield in arid and semi-arid areas. With increasing demand for irrigation water, alternative sources are being sought. Seawater salinity was previously considered unusable for irrigation. However, this water can be used successfully to grow crops under certain conditions. Amino acids is well known biostimulant which has positive effects on plant growth and yield, and significantly mitigates the injuries caused by abiotic stresses. Therefore, in the present study, the effect of exogenously treatment amino acid on faba bean plant growing under seawater salt stress was investigated. Reduction of salinity damage in faba bean by using a mixture of amino acids to improve morphological and biochemical parameters, and thus raising the level of plant yield was tested. A pot experiment was conducted to alleviate the harmful effects of seawater salinity on faba bean cv. Giza 843 by foliar spraying of an amino acid mixture with different concentrations (0.0, 500, 1000 or 1500 mg L-1). Irrigation of faba bean plants with seawater levels of 3.13 and 6.25 dS m-1 led to significant reductions in shoot length, number of leaves per plant, fresh and dry weight of shoots, photosynthetic pigments, total carbohydrates, polysaccharides, nucleic acid DNA and RNA contents of faba bean leaves. Seawater salinity induced higher contents of Na+ and Cl- and decreased contents of K+, K+:Na+, Ca2+, Mg2+ and P3+. Irrigation of faba bean plant with different levels of seawater decreased seed yield and total dry weight per plant compared with those irrigated with tap water. Also, total carbohydrates and total protein contents in seeds were reduced by increased seawater salinity levels. Amino acid application as foliar spray significantly improved all the reduced parameters due to seawater stress. However, the highest level of amino acid of 1500 mg L-1 exerted the strongest effect in alleviating the harmful effect of seawater salinity stress.